Impact of Histological Chorioamnionitis on Tracheal Aspirate Cytokines in Premature Infants - Aghai, Zubair H.; Camacho, Jeanette; Saslow, Judy G.; Mody, Kartik; Eydelman, Riva; Bhat, Vishwanath; Stahl, Gary; Pyon, Kee; Bhandari, Vineet (American Journal of Perinatology, 2012)
Background Histological chorioamnionitis (CHORIO) may increase inflammatory mediators in the lungs of preterm infants.Objective To study the impact of CHORIO on tracheal aspirate (TA) cytokines in ventilated infants.Design/Methods TA samples collected within 48 hours after birth from 40 ventilated neonates (gestational age [GA] <30 weeks, body weight [BW] <1250 g) were analyzed. Levels of 12 cytokines (interleukin [IL]-1α, IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, epidermal growth factor [EGF], interferon-γ [IFN-γ], monocyte chemotactic protein-1 [MCP-1], tumor necrosis factor-α [TNF-α], vascular endothelial growth factor [VEGF]) were measured using a biochip multianalyte immunoassay (Randox Laboratories, Antrim, UK). Total protein was measured by the Bradford assay. CHORIO assessment was done by a blinded pathologist.Results Twenty-six infants (GA 26.6 ± 1.4 weeks, BW 852 ± 162 g) had no CHORIO and 14 (GA 25.1 ± 1.0 weeks, BW 776 ± 164 g) had CHORIO. IL-1α, IL-1β, IL-8, and VEGF were significantly higher in TA of infants with CHORIO. After correction for dilution, IL-1α, IL-1β, and IL-8 were significantly elevated. Increased TA total cell count correlated with CHORIO, VEGF, EGF, MCP-1, IL-8, and IL-6 TA levels (all p ≤ 0.02). Ventilator, oxygen supplementation, and hospital days correlated with TA IFN-γ levels (all p ≤ 0.01).Conclusion CHORIO is associated with increased specific proinflammatory mediators in TA samples of preterm infants.
Keywords: inflammatory mediators; placenta; neonate; lung